2021
DOI: 10.3390/nu13124230
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Elemental and Elemental Formulas for Enteral Nutrition in Infants and Children with Medical Complexity—Thinking about Cow’s Milk Allergy and Beyond

Abstract: Children with medical complexities, such as multi-system disorders and/or neurological impairments, often experience feeding difficulties and need enteral nutrition. They frequently have impaired motility and digestive–absorbing functions related to their underlying condition. If a cow’s milk allergy (CMA) occurs as a comorbidity, it is often misdiagnosed, due to the symptoms’ overlap. Many of the commercialized mixtures intended for enteral nutrition are composed of partially hydrolyzed cow’s milk proteins, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Recently, several studies have reported a significantly higher prevalence of allergy in children with SMIDs receiving EN than in healthy individuals 22 . Kurihara et al found that the positive rate of latex‐specific immunoglobulin E was higher in patients with SMIDs than in healthcare professionals (25.9% vs 16.9%, respectively) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have reported a significantly higher prevalence of allergy in children with SMIDs receiving EN than in healthy individuals 22 . Kurihara et al found that the positive rate of latex‐specific immunoglobulin E was higher in patients with SMIDs than in healthcare professionals (25.9% vs 16.9%, respectively) 23 .…”
Section: Discussionmentioning
confidence: 99%
“…These formulas are available in both standard and high‐calorie forms (1.0 kcal/ml vs 1.2 and 1.5 kcal/ml), with and without fiber, and in a variety of flavors. Applications include children aged 1–13 years with intolerance to polymeric/intact protein formulas or in those with altered gastrointestinal tract function 9,15 . There is at least one product designated as a high‐protein formula, containing 16% of calories from protein.…”
Section: Formula Categoriesmentioning
confidence: 99%
“…Formulas may contain other allergens, and careful attention to the label and packaging is imperative to ensure safety 11 . One must pay close attention to carbohydrate, fat, and protein content of formulas to identify potential allergens as well as intolerances 15 …”
Section: Formula Selection: Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, hydrolyzed milk formulas (HF), which include partially hydrolyzed formula (pHF) and extensively hydrolyzed formula (eHF), have been recommended in many countries for the potential prevention of allergic diseases in infants at high risk of atopy who cannot be breastfed [67,68]. However, a recent meta-analysis does not support this recommendation, especially regarding asthma prevention.…”
Section: Use Of Hydrolyzed Infant Formulasmentioning
confidence: 99%